Development of Data Bank Application at the Agriculture and Plantation Service of West Nusa Tenggara Using the Prototyping Method - Agus Gunawan; Dwi Ratnasari; Sri Endang Anjarwani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2026)
This research aims to develop a Data Bank application that can assist Information and Documentation Management Officers (PPID) in providing public information services more quickly, accurately, and in a structured manner. This application is designed to address the problem of data management spread across various sectors, as well as delays in delivering information to the public. Development was carried out using a prototyping method, with direct user involvement in the design, testing, and evaluation processes of the system. The developed Data Bank application has several key features, including: storing and searching agricultural commodity data by category and year, data visualization in the form of interactive graphs, grouping data by district/city area, and an integrated information management system across sectors. This application is also equipped with data export, graph printing, and dynamic filtering features to facilitate information access by PPID officers and the public. System testing covered six aspects: functionality, performance, security and reliability, user interface (UI), user experience (UX), and its impact on PPID officer performance. The results showed that the Data Bank application successfully met all tested aspects with a user satisfaction level reaching 89%. This application is able to accelerate the process of providing information, improve work efficiency, and facilitate data storage and retrieval. Thus, the Data Bank application has been proven to support improving the quality of public information services within the NTB Agriculture and Plantation Service.